A review of the Pacific sleeper shark Somniosus pacificus: biology and fishery interactions - Mary Elizabeth Matta; Cindy A. Tribuzio; Lindsay N. K. Davidson; Keith R. Fuller; Garrett C. Dunne; Allen H. Andrews (Polar Biology, 2024)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Delineation of the Genera Haemoproteus and Plasmodium Using RNA-Seq and Multi-gene Phylogenetics - Jasper Toscani Field; Josh Weinberg; Staffan Bensch; Nubia E. Matta; Gediminas Valkiūnas; Ravinder N. M. Sehgal (Journal of Molecular Evolution, 2018)

Electrophoretic variation in seed proteins and interrelationships of species in the genus Oryza - Arvinder Singh; Yogesh Kumar; N. K. Matta (Genetic Resources and Crop Evolution, 2018)

Dietary Exposure to Tebuconazole Affects Testicular and Epididymal Histomorphometry in Frugivorous Bats - Mariana Machado-Neves; Mário J. O. Neto; Diane C. Miranda; Ana Cláudia F. Souza; Mariana M. Castro; Marcela N. Sertorio; Túlio F. Carvalho; Sérgio L. P. Matta; Mariella B. Freitas (Bulletin of Environmental Contamination and Toxicology, 2018)

Phylogenetic relationship and germplasm evaluation of different taxa of the genus Cucurbita using seed storage protein profiling - N. P. Singh; N. K. Matta (Plant Biosystems, 2016)

The Relationship Between Ovarioles Number and Female Size in Blackflies of the High Andes of Colombia - L A Esquivel; L I Moncada; C A Panza; I G Camacho; F A Colorado; N E Matta (Neotropical Entomology, 2015)

Holocene uplifted coral reefs in Lanyu and Lutao Islands to the southeast of Taiwan - S. Inoue; H. Kayanne; N. Matta; W. S. Chen; Y. Ikeda (Coral Reefs, 2011)

Levels of seed proteins in Citrullus and Praecitrullus accessions - N. P. Singh; N. K. Matta (Plant Systematics and Evolution, 2010)

Variation studies on seed storage proteins and phylogenetics of the genus Cucumis - N. P. Singh; N. K. Matta (Plant Systematics and Evolution, 2008)

Chickpea Seed Proteins as Affected by Mineral Supply Levels - Ranjeet Singh; N. K. Matta (Journal of Plant Biochemistry and Biotechnology, 2005)

Status of Mungbean Protein Fractions Under Changing Nutrient Regime - Sushil Kumar; N. K. Matta (Journal of Plant Biochemistry and Biotechnology, 1997)